KARDIOCHIRURGIA DOROSŁYCHPhysical ability and psychosocial functioning of patients qualified for coronary artery bypass graft surgery - Płaszewska-Żywko, Lucyna; Myrdko, Urszula (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduction: Advanced morbus ischaemicus cordis leads to gradual impairment in physical condition of the patients and could negatively influence their emotional status and role performance. The aim of the study was to assess the physical and psychosocial functioning of patients qualified for coronary artery bypass grafting (CABG). Material and Methods: The study group consisted of 112 patients (82% males), aged 30-81 years. The following tools were used: 1) questionnaire, 2) Canadian Cardiovascular Society (CCS) grading of angina pectoris scale, 3) Dartmouth COOP Function Charts (DCFC) assessing physical and emotional condition, social activity, pain, self-assessment of health and social support, 4) Geriatric Depression Scale, 5) Function Social Support Questionnaire, 6) medical record analysis. Results: The majority of the study group (58%) had reduced EF<50% and impaired physical ability (47.3% on DCFC scale, 53% on CCS scale). Pain negatively influenced quality of life (p=0.007) and self-assessment of health (p<0.001) and increased the risk of depression. In half of the group the disease caused a reduction in social activities and impairment in emotional status. Conclusions: Physical condition of the patients waiting for CABG is highly impaired and it has negative effects on health assessment and emotional status. There are difficulties in social life in a considerable number of patients.